2015
DOI: 10.1016/j.socec.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Generosity and sharing among villagers: Do women give more?

Abstract: a b s t r a c tThis paper explores generosity among anonymous villagers and sharing within families using a dictator game field experiment that was carried out in rural villages in Ethiopia. We find that generosity among anonymous villagers is very low compared with the findings in the dictator game literature. On average, the dictators in our sample allocate only 6% of their endowments to anonymous persons in the village, and 73% of the dictators keep all of their endowments to themselves when paired with ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Confirming common belief, dictator giving is typically found to be greater among spouses than with anonymous strangers [9]. Married couples have also demonstrated greater cooperation [10], trust [11] and reciprocity [12].…”
Section: Introductionmentioning
confidence: 85%
“…Confirming common belief, dictator giving is typically found to be greater among spouses than with anonymous strangers [9]. Married couples have also demonstrated greater cooperation [10], trust [11] and reciprocity [12].…”
Section: Introductionmentioning
confidence: 85%
“…As gender differences vary across countries, and sometimes within countries, it is important to increase the existing knowledge of gender differences using country-specific or region-specific information to avoid generalizing narratives that may prove inefficient, especially when prescribing appropriate gender intervention frameworks (Peterman et al 2014). Bezu and Holden (2015), for example, performed dictator game experiments in poor rural villages in the patriarchal African society of Ethiopia. Examining whether there were gender-based differences in terms of generosity, they found that women were not more generous than their male counterparts towards anonymous villagers.…”
Section: Introductionmentioning
confidence: 99%